STOKES FLOW INDUCED DRAG AND TORQUE ON ASBESTOS-LIKE FIBRES CANNOT BE ESTIMATED BY A SIMPLISTIC ELLIPSOIDAL APPROXIMATION - Ravnik, Jure; Štrakl, Mitja; Wedel, Jana; Steinmann, Paul; Hriberšek, Matjaž (WIT Transactions on Engineering Sciences, 2022)
In this paper we present an algorithm based on the Boundary Element Method for solving the Stokes flow around an arbitrarily shaped particle in multiphase flows. The objective of the algorithm is to determine the exact drag force and torque experienced by the particle during its motion in a turbulent flow field. The developed method is used to compare the predicted force and torque values on a realistic 3D model of a mineral fibre and its simplifying ellipsoidal approximation. We found that the force and torque values calculated for the real particle geometry differ greatly from the values obtained with the simplifying ellipsoidal approximation. On average, a relative error of less than 10% is achieved for only 10%–30% of the particle orientations.
CRIS-Team Scopus Importer:2022-09-16
Keywords: asbestos; boundary element method; Lagrangian simulation; mineral; multiphase flows; muscovite